Chinese radicals as distinctive marks of language. (June 2019) - Nie, Hongyin
People of the southern ethnic minorities in China used to create their own scripts by imitating Chinese characters, in which some inherent Chinese radicals are borrowed, which indicate how the characters should be read semantically in their native language rather than in Chinese. This method, unexplainable by traditional Chinese theory, may not be regarded as a valid way of character creation, but proves to be an ignored fact existing in the "Southern Scripts of Chinese Imitation".